The green road ebook A novel. - Enright, Anne (2015)
One of the Guardian's 100 Best Books of the 21st Century "With language so vibrant it practically has a pulse, Enright makes an exquisitely drawn case for the possibility of growth, love and transformation at any age." —People From internationally acclaimed author Anne Enright comes a shattering novel set in a small town on Ireland's Atlantic coast. The Green Road is a tale of family and fracture, compassion and selfishness—a book about the gaps in the human heart and how we strive to fill them. Spanning thirty years, The Green Road tells the story of Rosaleen, matriarch of the Madigans, a family on the cusp of either coming together or falling irreparably apart. As they grow up, Rosaleen's four children leave the west of Ireland for lives they could have never imagined in Dublin, New York, and Mali, West Africa. In her early old age their difficult, wonderful mother announces that she's decided to sell the house and divide the proceeds. Her adult children come back for a last Christmas, with the feeling that their childhoods are being erased, their personal history bought and sold. A profoundly moving work about a family's desperate attempt to recover the relationships they've lost and forge the ones they never had, The Green Road is Enright's most mature, accomplished, and unforgettable novel to date.